(untitled) (Research, Society and Development, 2020)
The soybean crop often presents limitations on yield, many of which stem from nutritional problems, mainly due to insufficient supply of N. One of the ways to overcome this problem is through co-inoculation with plant growth promoting bacteria (PGPB), in order to potentiate the BNF and facilitate the acquisition of N and other nutrients in the soil. Thus, the aim of this study was to evaluate the effect of co-inoculation, between B. japonicum and PGPB, on yield, nodulation and yield components of soybean crop. Four experiments were carried out in the 2017/18 crop season, the tests were carried out in randomized blocks in a 4 x 12 factorial scheme, being: four (4) locations (Guarapuava/PR, Lapa/PR, Santa Maria do Oeste/PR and Sertão/RS) and 12 treatments (use of PGPB associated with standard inoculation). Yield, nodulation and yield components of soybean were evaluated. The results obtained, although mostly positive, were variable depending on each location, the variability of the results can be reduced with bacterial pools. PGPB’s provided increases in mass and number of nodules, mass of a thousand grains, number of grains per plant, and these characteristics are directly related to the yield of the crop. It was observed that the PGPB, in co-inoculation with B. japonicum, mainly of the Bacillus genus, provided increases in productivity in the soybean culture, soon they showed themselves as an important alternative to be used in co-inoculation with B. japonicum in the soybean crop.